Incentive Bidding for Mobile Investment : Economic Consequences and Potential Responses - Charlton, Andrew, (Andrew Henry George), 1978-; Organisation for Economic Co-operation and Development (Paris : OECD Publishing, 2003)
Competition among governments to attract foreign direct investment (FDI) has grown significantly. This paper investigates the extent to which the size of incentive packages offered to investors by governments is driven by competitive pressure to attract mobile investment projects. It finds that such competition is in many cases a significant determinant of the size and nature of investment incentives. Competition can have both positive and negative effects on domestic and international welfare. Negative outcomes typically occur when governments offer attraction packages that are larger than the value of the benefits to the host economy, or when governments resort to inefficient incentive instruments. Increased transparency would significantly reduce the scope for negative welfare outcomes. Proper accounting for incentives helps to ensure that expenditure is aligned with policy goals, reduces the potential for corruption and improves the efficiency of the negotiation process ...
Keywords: Investments